RECHARGE MECHANISM AND HYDROCHEMISTRY EVALUATION OF GROUNDWATER IN THE NUAIMEH AREA, JORDAN, USING ENVIRONMENTAL ISOTOPE TECHNIQUES - Bajjali W. (My University, 2006)
The relationship between the stable isotopic and chemical composition of precipitation and groundwater was studied in the Nuaimeh area of the Ajloun Highlands in Jordan. The isotopic composition values of precipitation and groundwater are almost identical. The spatial variation of stable isotopes in precipitation is mainly due to the effect of seasonal temperature, altitude and amount. The groundwater reveals identical variation in isotopic composition to the precipitation due to direct recharge and the karstic nature of the outcropping Turonian aquifer. Tritium levels in wells are high and their content is similar to the weighted mean value of tritium content in precipitation, indicating local recharge and low residence time. The 14C activity in the tritiated groundwater is found to be about half of the 14C activity of precipitation in the region. A geochemical evolution through dissolution of carbonate by water–carbonate rock interactions reduced the atmospheric 14C activity from 114 to 61 pmc in the groundwater. A 14C of around 61 pmc and 7.6 TU values are considered the initial concentration for the recharge in the shallow carbonate aquifer in the Yarmouk Basin. The large fluctuation of water level in observation wells during the rainy season indicates the sensitivity and direct response of the aquifer to the recharge. The chemical composition of the groundwater (Ca2+–HCO3−) gives emphasis to the short duration of water–rock interaction and indicates dissolution of the carbonate aquifer. The elevated concentrations of Cl− and NO3− in groundwater are attributed to anthropogenic sources.
Keywords: GROUNDWATER AGE; HYDROCHEMISTRY; ENVIRONMENTAL ISOTOPES; CONTAMINATION; WATER-ROCK INTERACTION; Turonian; Mesozoic::Cretaceous::Upper::Turonian; Мезозой::Меловая::Верхний::Туронский